Surrogatarrangemang, moderskap och nationalitet. Finlands riksdags debatter om legaliseringen av surrogatarrangemang - Kanckos, Lise (K&K - Kultur og Klasse, 2012)
Surrogacy, motherhood and nationality | Surrogacy arrangements were allowed in Finland, and were practiced to a small extent at four clinics, before the Act on Assisted Reproduction took effect on 1 September 2007. The political debate on surrogacy was at times lively during the preparations of the law. This article is based on a rhetoric and discourse analysis of discussions on surrogacy, maternity and nationality in the Finnish parliamentary debates concerning the legalisation of surrogacy. The material consists of three debates in 2002, 2006 and 2007, newspaper articles, a medical article and the website of a discussion forum. Surrogacy arrangements in Finland were often constructed in these debates as safe and controlled, and the Finnish surrogate was described as altruistic, while surrogates in other countries were constructed as rented wombs. These political discourses on surrogacy are also discussed in relation to a wider context of cross-border reproductive care and consumption.